Visual-Spatial and Intrapersonal Intelligence: Identification Its Role in The Learning Outcomes of Students in Islamic Schools - Abdi, Abdul Wahab (Universitas Pendidikan Indonesia, 2020)
This study aims to identification of visual-spatial intelligence and intrapersonal intelligence and their relationship to the learning outcomes of social studies students of Islamic school. The study population was students of Al Azhar Islamic Junior High School Banda Aceh, Indonesia and taken a sample of 50 students using random sampling techniques. The results of the multiple correlation coefficient analysis are 0.375, which means that there is a low relationship. The effect of being given visual-spatial intelligence and intrapersonal intelligence with social studies learning outcomes is 14.07% and the remaining 85.93% is influenced by other variables outside the research. Hypothesis testing shows that there is a significant relationship between visual-spatial intelligence and intrapersonal intelligence with learning outcomes of social studies. This finding is expected to be used by teachers in developing learning methods that can hone various types of intelligence in students to provide an influence for improving learning outcomes